ADSORPSI KALSIUM AIR PAYAU SEBAGAI SUMBER AIR BERSIH BAGI MASYARAKAT PESISIR DENGAN SILIKA TERMODIFIKASI DARI ABU SEKAM PADI - Kahar, Kaharuddin; Edihar, Muh; Harimu, La; Dahlan; Mutmainnah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2025)
Many Indonesian residents have difficulty obtaining clean water, especially people who live in coastal areas. Those who live there can only consume brackish water which is considered to have side effects on health due to the excessive calcium content. This research offers a simple method, namely adsorption using abundant raw materials, namely rice husk ash from agricultural waste resulting from burning rice husks. Using husks directly has less effectiveness, so it needs to go through additional processes such as removing impurities and modifying the structure. This research aims to reduce calcium levels in brackish water using silica that has been modified from rice husk ash. The process of making adsorbents is carried out by sieving, heating, filtering, washing to obtain silica, then modifying and optimizing important parameters until its application to brackish water. The difference between pre-modified and modified silica can be seen in the characterization with FTRI at wave numbers from 470 cm-1 to 430 cm-1 1, namely deeper bending vibrations, which are also clarified by the surface condition with more structured pores seen in the SEM results. The modified silica works optimally at a mass of 0.4 grams, pH 7.5, contact time of 40 minutes and concentration of 50 ppm. It has an adsorption capacity of 3.2 mg/g and follows the Langmuir isotherm pattern.